Salmone, pesce spada e tonno : a taglio 'carpaccio' e confezionato sottovuoto - M.A. Paleari; C. Bersani; G. Beretta; S. Pirani (Chiriotti, 2009)
The consumption of raw fish, widespread in Japan, is now spreading to Western countries; however the fact that fish can be conserved in the fresh state for only 4 days at 4°C affects the preparation of such products. Thus we set out to define, for three fish species, salmon (Salmo salar), swordfish (Xiphias gladius) and tuna (Tunnus albacares), the average shelf-life of the thin, vacuum packed, raw slices used for fish ‘carpaccio’. Treatment with brine (30% NaCl) mixed with citric acid and sodium benzoate, together with a short drying period, forms the basis of the technological proposal to extend their shelf-life. An evaluation was made of the microbiological state and several chemical parameters to assess their keeping after 0,15,30,45 and 60 days of storage at 4-6°C. It was found that, from the point of view of consumer health, the results were satisfactory for a shelf life of 40-45 days.